OBENTOU KREASIKU - Maharani Patria Ratna (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
This contribution to society event (PKM)’s theme is about making bentou. The object are children of GKI. This event is supported by the PKM team and GKI as a partner. This event has given a lot of contributions besides the skill of making bentou. The other contributions are improving children’s creativity, improving soft skill, and also improving children meticulous, etc. The output of this event is bentou as a product.